The role of TGF-β in the development of lung cancer in patients with chronic obstructive pulmonary disease - Hatice Celik Tuglu; Onder Ozturk; Pınar Aslan Kosar (Advances in Biomarker Sciences and Technology)
Background: Lung cancer and chronic obstructive pulmonary disease (COPD) have similar etiologic factors, but the relationship between these diseases has not been investigated. This study aimed to investigate whether TGF-β polymorphisms it is influential in the development of lung cancer in COPD patients or not. Methods: Seventy-eight patients were divided into three groups; group Ⅰ: 28 patients with COPD and lung cancer, group Ⅱ: 30 patients with COPD, and group Ⅲ: 20 healthy people as a control group. We investigated 10 TGF-β polymorphisms in these patients over the age of 40 who were not relatives. Demographic data and polymorphism results were evaluated by an online access program provided by the Institute of Human Genetics using the Statistical Package for the Social Sciences v.22.0 program and the DeFinetti program provided by an online resource using the Armitage trend test. Results: Wild alleles were dominant in healthy individuals; rs11466345 T > C, rs1800470-2 G > C, rs1800471-1 C > G, rs1800471-2 C > T, and rs1877474-2 T > G polymorphisms. They were not associated with lung cancer and COPD development. However, rs1800470–1 G > A and rs1800469 A > G polymorphisms might have protective effects against lung cancer development, and rs1800470–1 G > A polymorphism could be more protective in former smokers than in smokers. If further studies confirm these findings, rs1800470–1 G > A and rs1800469 A > G may serve as protective factors against lung cancer development. Additionally, rs1800470-1 G > A polymorphism may provide greater protective effects against lung cancer in former smokers compared to current smokers. Conclusions: According to our study, although some TGF-β polymorphisms may be protective against lung cancer development in COPD patients, the limited sample size—especially in the control group—and inclusion of only male participants restrict the statistical power and generalizability of these findings. Nonetheless, we believe our results provide valuable preliminary insights that may guide future research. Larger, more diverse studies are needed to confirm and expand upon these findings.